Directed Non-targeted Mass Spectrometry and Chemical Networking for Discovery of Eicosanoids and Related Oxylipins - Watrous JD; Niiranen TJ; Lagerborg KA; Henglin M; Xu YJ; Rong J; Sharma S; Vasan RS; Larson MG; Armando A; Mora S; Quehenberger O; et al. (CELL PRESS, 2022)
Eicosanoids and related oxylipins are critical, small bioactive mediators of human physiology and inflammation. While similar to 1,100 distinct species have been predicted to exist, to date, less than 150 of these molecules have been measured in humans, limiting our understanding of their role in human biology. Using a directed non-targeted mass spectrometry approach in conjunction with chemical networking of spectral fragmentation patterns, we find over 500 discrete chemical signals highly consistent with known and putative eicosanoids and related oxylipins in human plasma including 46 putative molecules not previously described. In plasma samples from 1,500 individuals, we find members of this expanded oxylipin library hold close association with markers of inflammation, as well as clinical characteristics linked with inflammation, including advancing age and obesity. These experimental and computational approaches enable discovery of new chemical entities and will shed important insight into the role of bioactive molecules in human health and disease.